Application of modern computer algebra systems in food formulations and development: A case study. (June 2017) - Musina, Olga; Putnik, Predrag; Koubaa, Mohamed; Barba, Francisco J.; Greiner, Ralf; Granato, Daniel; Roohinejad, Shahin
Abstract: Background: Nutritional security determines the level of public health within a population while inadequate nutrition is one of the major factors in development of various health problems. This can be alleviated with sufficient and affordable access to currently available or newly designed nutritious foods. Scope and approach: Formulation of new foods can be very costly, so methods able to lower design expanses are of utmost importance to the industry. Hence, the purpose of this work was to rationalize utilization of modern computerized algebraic systems (CAS) in solving traditional problems for formulating food mixtures by food combinatoric principles (FCP). Key findings and conclusions: Practical aspect of FCP approach was shown in a case of formulating new food with predefined nutritional features (targeting amino acids content) from 14 components (curd and 13 varieties of grains and beans). The application of FCP in CAS saves time and provides mathematically perfect solutions. Such solutions should be tested for supplementary production parameters (sensory, feasibility, etc.) prior to industrial production of large scale quantities. Highlights: New product development is an expensive, complex and time-consuming task. Computer software provides a quick and reliable way to calculate mix recipes. Modern computerized algebraic systems can be used to formulate food mixtures. Food combinatoric principles can prepare foods with predefined nutritional features.